Implementasi UNSCR 1325 tentang Perempuan Korban Konflik Bersenjata Donbass oleh Pemerintah Ukraina - HABFIE, ULZANA; Wahyudi, Fendy Eko (Journal of International Relations, 2021)
This study intend to analyze state’s compliance in carrying out the objectives of UNSCR 1325 (2000) in regards of women in a situation of conflict. The armed conflict emerged on eastern Ukraine, often called by War in Donbass, which was started on 2014 up until its sixth year has yet come to an end. The conflict has affected thousands of people being victims of its violence, both combatans and civilians. The situation is negatively affecting civilians especially women those who live and stay in the conflict zone. Women are considered most vulnerable when it comes to armed conflict, for the higher risks of receiving physical, sexual, economical, and even social violence. The low participation rate of women in peace processes is also becoming the concern in women protection and participation agenda in a situation of conflict. The objective of this study is to analyze the government of Ukraine’s compliance to UNSCR 1325 agendas in regards of women in conflict and how Ukraine government complies on implementing it. The author will use descriptive method, compliance theory by Ronald B Mitchell and the public policy trichotomy indicators (outputs, outcomes, impacts) as the research framework. This study described that the government of Ukraine have implemented the output indicator by adopting UNSCR 1325 (2000) as its National Action Plan, two years after the conflict emerged, whose agendas aligned with the UNSCR 1325 (2000)’s agendas itself.